2006
DOI: 10.2106/jbjs.e.00272
|View full text |Cite
|
Sign up to set email alerts
|

How Many Patients? How Many Limbs? Analysis of Patients or Limbs in the Orthopaedic Literature: A Systematic Review

Abstract: Our findings suggest that a high proportion (42%) of clinical studies in high-impact-factor orthopaedic journals involve the inappropriate use of multiple observations from single individuals, potentially biasing results. Orthopaedic researchers should attend to this issue when reporting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 4 publications
0
96
0
Order By: Relevance
“…In a systematic review of orthopaedic literature, Bryant et al [2] found that 42% of clinical studies in high-impact-factor orthopaedic journals had inappropriately used multiple observations from single individuals. In clubfoot research, Duffy et al [7] combined multiple data from single individuals noting that an earlier study had observed no difference in findings when excluding data of one foot in bilateral clubfeet cases; however, this study had used statistical methods that assumed that each data point was independent [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of orthopaedic literature, Bryant et al [2] found that 42% of clinical studies in high-impact-factor orthopaedic journals had inappropriately used multiple observations from single individuals. In clubfoot research, Duffy et al [7] combined multiple data from single individuals noting that an earlier study had observed no difference in findings when excluding data of one foot in bilateral clubfeet cases; however, this study had used statistical methods that assumed that each data point was independent [16].…”
Section: Discussionmentioning
confidence: 99%
“…It would not be assumed that the contralateral breast in someone with BRCA(+) breast cancer were independent data points, and it has been shown that they are not independent [5]. It has also been shown that multiple measurements taken from one patient (eg, two feet in bilateral cases) are more likely to be correlated than measurements taken from single limbs of multiple patients [2,13]. To determine the correct analysis for clubfoot trials, any correlation between the feet of bilateral cases first needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…After operative report and medical record screening, we included all 927 patients older than 18 years who had surgery for a pathologic or impending metastatic long bone fracture between January 1999 and December 2013. We included only the first surgery per patient if patients underwent multiple operations on different occasions so as to not violate the statistical assumption of independence [3]. We defined long bones as the femur, humerus, tibia, fibula, radius, and ulna; multiple long bones operated on during the same procedure were categorized separately.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous articles and reviews explore the basics of research methodology to provide a sound understanding of proper design and conduct of studies [1,2,5,7,8,11,15]. Associations found in trials, however, may derive from four sources: chance, bias, confounding, or a true effect.…”
Section: Introductionmentioning
confidence: 99%